2021
DOI: 10.1213/ane.0000000000005443
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Contrast Agents in Interventional Pain Procedures: A Multispecialty and Multisociety Practice Advisory on Nephrogenic Systemic Fibrosis, Gadolinium Deposition in the Brain, Encephalopathy After Unintentional Intrathecal Gadolinium Injection, and Hypersensitivity Reactions

Abstract: This Practice Advisory presents a comprehensive and evidence-based set of position statements and recommendations for the use of contrast media in interventional pain procedures. The advisory was established by an international panel of experts under the auspices of 11 multinational and multispecialty organizations based on a comprehensive review of the literature up to December 31, 2019. The advisory discusses the risks of using gadolinium-based contrast agents. These include nephrogenic systemic fibrosis, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…In those with documented moderate or severe hypersensitivity reactions, pretreatment and injection with a different, low-osmolar non-ionic agent can be considered for those with a contraindication to gadolinium. 240 A recent cohort study conducted in the Medicare population on serious spinal adverse events of epidural corticosteroid injections failed to demonstrate that non-particulate corticosteroids had lower event rates than particulate steroids. 232 Alternatively, a injection can be considered when a transforaminal injection is deemed too risky.…”
Section: Practical Recommendations Epidural Corticosteroid Administra...mentioning
confidence: 99%
See 1 more Smart Citation
“…In those with documented moderate or severe hypersensitivity reactions, pretreatment and injection with a different, low-osmolar non-ionic agent can be considered for those with a contraindication to gadolinium. 240 A recent cohort study conducted in the Medicare population on serious spinal adverse events of epidural corticosteroid injections failed to demonstrate that non-particulate corticosteroids had lower event rates than particulate steroids. 232 Alternatively, a injection can be considered when a transforaminal injection is deemed too risky.…”
Section: Practical Recommendations Epidural Corticosteroid Administra...mentioning
confidence: 99%
“…In the event of a documented contrast allergy, earlier guidelines recommended using preservative‐free dexamethasone 111,238,239 More recent multispecialty guidelines recommend the consideration of pretreatment with glucocorticosteroids, sometimes with antihistamine, in individuals with a mild documented contrast allergy and injection with a different, low‐osmolar non‐ionic contrast agent. In those with documented moderate or severe hypersensitivity reactions, pretreatment and injection with a different, low‐osmolar non‐ionic agent can be considered for those with a contraindication to gadolinium 240 …”
Section: Techniquesmentioning
confidence: 99%
“…This approach has two drawbacks; namely (1) the indirect assessment of the ECM based on secondary changes in extracellular water volume, and (2) that it poses safety risks due to the use of potentially nephrotoxic gadolinium chelates (Benzon et al . 2021). Rather than perform conventional MR imaging, measurement of T1ρ relaxation time holds promise for imaging of the muscle ECM as a more direct method for assessing macromolecular ECM content.…”
Section: Introductionmentioning
confidence: 99%
“…Given the reports of adverse events,46 47 a multisociety working group published recommendations regarding the use of GBCAs in interventional pain procedures 48. The working group concluded that GBCAs are contraindicated in intrathecal (IT) injections.…”
Section: Discussionmentioning
confidence: 99%
“…GBCAs may potentially be used in procedures in which there is a low risk of IT injection including lumbar sympathetic blocks, facet joint injections, and MBBs after careful explanation to the patient of the risks and the off-label utilization. The group also recommend using the lowest possible dose of GBCA when necessary to achieve clinical information when necessary 48. A recent meta-analysis reviewed incidences of adverse outcomes following intrathecal administration of GBCA 49.…”
Section: Discussionmentioning
confidence: 99%